SHORT COMMUNICATION: On Scientific Publications - EDUARDO AGUSTIN PADLAN (Microbiology Indonesia, 2007)
Maybe we can make our local journals internationally “visible” and thus be included in international indices (the sign of international recognition). That may not be too difficult to achieve. If we could convince our more productive local scientists and our compatriots abroad, who are able toproduce internationally competitive results, to publish seminal papers or review papers in local journals and afterwards cite those (local) papers in their other (international) publications, then the internationalcommunity will become aware of our local science and our local journals.